Enthalpy-driven micellization of oligocarbonate-fluorene end-functionalized Poly(ethylene glycol). (3rd January 2018) - Wei, Guangmin; Venkataraman, Shrinivas; Yang, Yi Yan; Hedrick, James L.; Prabhu, Vivek M.
Abstract: A fluorescent pyrene probe method was applied to measure the critical micelle concentration ( CMC ) of oligocarbonate-fluorene end-functionalized poly(ethylene glycol) (Fm E445 Fm ) triblock copolymers in water. The CMC decreases with lower temperature and higher values of the hydrophobic block length, m . When analyzed by a closed-assembly micelle model, the estimated energetic parameters find a negative Δ H °mic and small positive Δ S °mic suggestive of enthalpy-driven micellization, which differs from entropy-driven oxyethylene/oxybutylene triblock copolymers and octaethylene glycol- n -alkyl ethers. The enthalpy-driven micellization of Fm E445 Fm may result from the limited hydration of individual hydrophobic F blocks that leads to few hydrogen-bonded waters released during F block association. The π-π stacking oligocarbonate-fluorene system also observed enthalpy-entropy compensation when compared to a series of published data on diblock and triblock copolymer systems. An anomalously low partition equilibrium constant for m = 15.3 implies a tightly-packed core that excludes pyrene intercalation into the fluorene core. This is discussed along with the possible limited applicability to estimate the CMC and potential model drug molecule insertions into the intercalated micelle core. Graphical abstract: Image 1 Highlights: The CMC of supramolecular assembled polymers increases with temperature; differing from commercial polymer amphiphiles. A trade-off to achieve low CMC and high partition coefficient is controlled by pi-stacking groups. Enthalpy-entropy compensation is observed lying closer to the enthalpy-driven regime.